Development of Learning Video Media for Graphic Arts Courses of Relief Print in Department of Fine Arts - Ega Harna B; Ramalis Hakim (Postgraduate School, Universitas Negeri Padang, 2022)
The development of technology and information is progressing very rapidly and is seen in various fields of life without exception in the world of education. Learning that is highly dependent on technology, as it is today, is becoming a challenge for both learners and educators who have a dominant background in practice learning materials such as in the fine arts department at universities. To improve the learning process, learning outcomes, and the quality of education at universities majoring in fine arts, it is necessary to conduct development research. Writing this thesis aims to produce learning media that can support the learning process in the graphic arts course in the relief print technique in the fine arts department. The media produced is in the form of learning video media, which is believed to be able to increase the interest and learning outcomes of students at universities majoring in fine arts. This study uses research and development methods with the DDD-E model. The data obtained in this development research are sourced from the validity test, practicality test, and effectiveness test. The results of this research on the development of instructional video media reached the valid, practical, and effective categories by getting a good response by educators and students. The developed learning video media can also increase learners interest and learning outcomes and influence learners understanding.